Whole-Body versus Local DXA-Scan for the Diagnosis of Osteoporosis in COPD Patients - Lidwien Graat-Verboom; Martijn A. Spruit; Ben E. E. M. van den Borne; Frank W. J. M. Smeenk; Emiel F. M. Wouters (Journal of Osteoporosis, 2010)
Background. Osteoporosis is an extrapulmonary effect of chronic obstructive pulmonary disease (COPD). Diagnosis of osteoporosis is based on BMD measured by DXA-scan. The best location for BMD measurement in COPD has not been determined. Aim of this study was to assess whole-body BMD and BMD of the hip and lumbar spine (local DXA) in COPD patients and compare the prevalence of osteoporosis at these locations. Methods. Whole body as well as local DXA-scan were made in 168 COPD patients entering pulmonary rehabilitation. Patient-relevant characteristics were assessed. Prevalence of osteoporosis was determined. Characteristics of patients without osteoporosis were compared to patients with osteoporosis on local DXA. Results. A higher prevalence of osteoporosis was found using local DXA compared to whole-body DXA (39% versus 21%). One quarter of patients without osteoporosis on whole body-DXA did have osteoporosis on local DXA. Significant differences in patient characteristics between patients without osteoporosis based on both DXA measurements and patients with osteoporosis based on local DXA only were found. Conclusions. DXA of the hip and lumbar spine should be made to assess bone mineral density in COPD patients. The lowest T-score of these locations should be used to diagnose osteoporosis.